MAKRAME SEBAGAI ELEMEN ESTETIS JAM DINDING - NURMILA YANTI, Dra. Ernis, M.Pd., Drs. Erwin, M.Sn. (Universitas Negeri Padang, 2019)
Wall clock is one of the indispensable timepieces at home, or institutions such as schools, offices and so on. The exsistence of this wall clock also has other functions, it’s functions a timepiece also as an ornamental object (room decoration). Wall clock with displaying macrame techniques, it presents new and different forms, of course in awesome room when the clock is displaying.This creation aims to visualize the beauty of macrames on wall clocks. Inaddition, the creator wants to change the public’s view of this macrame that is so difficult in the process even though this macrame is easy and brings satisfaction to the audiences. The teqhnique that is used in malking this final work is by combining several knots in macrame teqhniques, which are a square knot and a souble half hook knot. After a long time of processes, 8 macrame works that have just been created are : 1) light surrounded by darkness, 2) between me and others, 3) my hobby, 4) sun flower, 5) my family, 6) uniting us, 7)my best friends, 8) my woman. Through this makrame works, these are hoped that it can arouse enthusiasm in the work of art, and be used as a reference for making better macrame in the future.Keywords: Wall clock, Macrame